The correlation of the understanding of Indonesian history, multiculturalism, and historical awareness to students’ nationalistic attitudes - Muhammad Basri; Johan Setiawan; Marzius Insani; Muhammad Rijal Fadli; Kian Amboro; Kuswono Kuswono (Institute of Advanced Engineering and Science, 2022)
This study aimed to analyze the relationship between understanding Indonesian history, multiculturalism, and historical awareness with the nationalist attitudes of state high school students in Yogyakarta. This type of research was correlational research with a quantitative approach. The sample consisted of 126 students. Data collection used tests and questionnaires. The test was used to reveal data about understanding of Indonesian history and multiculturalism, while the questionnaire was used for revealing students’ historical awareness and nationalistic attitudes. The validity of the instrument used a biserial point correlation test and a reliability test with the KR-20 formula. The data then were analyzed by using quantitative descriptive analysis technique. The pre-requisite analysis consisted of the normality test, linearity test and multicollinearity test. The hypothesis testing used Product Moment Correlation, multiple correlation, relative contribution, and effective contribution. The results showed that there is a positive and significant relationship between understanding of Indonesian history, multiculturalism, and historical awareness with students' nationalism. History learning will be much more meaningful if these four concepts are used as the objectives of history learning.